DEVELOPING MILLENNIAL DRAMA PERFORMANCE BASED-TEXTBOOK ON “SITI ZUBAIDAH” FOR UNDERGRADUATE EFL STUDENTS - Selly Septiandini; Rita Inderawati; Ismail Petrus; Nurhayati Nurhayati (University of Kuningan, 2022)
This study aimed at developing a dynamic teaching-learning process by integrating the millennial drama performance-based-textbook on “siti zubaidah” to improve students learning outcomes. The research design in this study was development research that covered the phases of analysis, design, evaluation, and revision. The data were collected through questionnaires, validity tests, and the effectiveness of the developed millennial drama performance based-textbook on “siti zubaidah” from South Sumatra through stages designed according to Akker models. The data were analyzed quantitatively and qualitatively. To determine its validity, practicality and potential effect of the product, a formative evaluation was conducted. The validity of the developed product was 4 (high validity). The product was evaluated in experts’ review related to instructional design and content. The practicality of the developed reading materials was evaluated in one to one evaluation (4.16), categorized into high category and small group evaluation (4.44) which categorized as very high practicality. In field test, the result was 90% which the developed product was regarded as a high potential effect. The millennial drama performance-based-textbook on “siti zubaidah” was potential to be applied for undergraduate EFL students because it became a basic reference to improve the students’ drama performance. Moreover, the textbook gave the students insight into one of the local cultures in Palembang, Sumatra Selatan.